Answer:
B. x(x) + (−6)(−3)
NOT equivalent to (x − 6)(x − 3)
Step-by-step explanation:
(x − 6)(x − 3)
= x^2 - 3x - 6x + 18
= x^2 - 9x + 18
A. (6 − x)(3 − x)
= 18 - 6x - 3x + x^2
= 18 - 9x + x^2
= x^2 - 9x + 18 ---->equivalent to (x − 6)(x − 3)
B. x(x) + (−6)(−3) = x^2 + 18 ----> NOT equivalent to (x − 6)(x − 3)
C. x2 − 3x − 6x + 18 = x^2 - 9x + 18 --> equivalent to (x − 6)(x − 3)
D. x(x − 6) − 3(x − 6)
= x^2 - 6x - 3x + 18
= x^2 - 9x + 18 ---->equivalent to (x − 6)(x − 3)
Answer:
Step-by-step explanation:
the both eual out to the same equation like how 3/4 equals 0.75 and 3/2 equals 1.5 well if you keep dividing sooner or later they will both be equal at the same number.
Note that x is the hypotenuse of a right triangle. Applying the Pyth. Thm.,
x^2 = 2^2 + 6^2, or x^2 = 4 + 36 = 40.
Thus, the hypotenuse is +sqrt(40), or 2sqrt(10).
Answer:
6*4+8=32
Step-by-step explanation:
32-8=24
24/6=4
so 6*4=24
24+8=32